Rutinitas Petani Arak Di Karangasem Bali Sebagai Ide Penciptaan Karya Seni Patung Naturalis - Suarsa, Si Ngurah; Mustika, I Ketut; Sukarya, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
The routine of arak farmers in Karangasem Bali is very interesting to be made an object of research on the creation of fine art (statues) with the title "Routines of Arak Farmers in Karangasem Bali as an Idea for Creating Naturalist Sculpture Art". To find out the problems of creation above, research steps, creation and presentation of art were carried out using the approach of art theory, aesthetics, construction and semiotics. The research approach uses a qualitative approach using the method of collecting observation data, interviews, documentation and literature studies. Results of the discussion: (1) the form of the statue from the representation of the routine of arak farmers in Karangasem Bali: (a) nadah tuak, (b) harvest tuak, (c) mulangin tuak, (d) ngedig lau, (e) nginum arak. (2) the technique used is the technique of adding and reducing materials. (3) the author displays the visual form of arak farmers who are carrying out daily activities or routines of the arak farmers, with a naturalistic style in each form of work emphasizing naturalness and beautifying without significantly changing the shape of the object. From this concept, 5 works were created that can be reviewed from the ideoplastic aspect and the physioplastic aspect. The output of this research is in the form of a thesis, five pieces of sculpture.